2022
DOI: 10.3390/agronomy12061405
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Scorching following Foliar Fertilization of Wheat with Urea or Urea–Ammonium Nitrate Is Caused by Ammonium Toxicity

Abstract: Foliar fertilization is a potential tool to increase the use-efficiency of nitrogen (N) fertilizers. However, whilst leaf scorching has frequently been reported, the underlying physiological processes are not clear. In the present work, we investigate the intensity of leaf scorching as affected by the balance between ammonium assimilation and accumulation. Leaves were sprayed with urea–ammonium nitrate (UAN) solution without surfactant or applied liquid droplets of urea in different N concentrations with surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…The highest number of effective tillers (18.67) was recorded in the T 8 treatment, which was statistically similar to the T 7 , T 6, and T 10 treatments, while the lowest (12.67) was in the T 1 treatment. The results of the present experiment agreed well with the findings of other researchers who concluded that foliar application of urea significantly increased the number of effective tillers hill –1 of BRRI dhan29. Foliar spraying of 3% urea solution produced a higher number of effective tillers hill –1 than 1% urea spraying . Soil (75%) and foliar (10%) application of urea significantly increased the effective tillers of Binahsail and BRRI dhan46 varieties during the T. aman season .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The highest number of effective tillers (18.67) was recorded in the T 8 treatment, which was statistically similar to the T 7 , T 6, and T 10 treatments, while the lowest (12.67) was in the T 1 treatment. The results of the present experiment agreed well with the findings of other researchers who concluded that foliar application of urea significantly increased the number of effective tillers hill –1 of BRRI dhan29. Foliar spraying of 3% urea solution produced a higher number of effective tillers hill –1 than 1% urea spraying . Soil (75%) and foliar (10%) application of urea significantly increased the effective tillers of Binahsail and BRRI dhan46 varieties during the T. aman season .…”
Section: Resultssupporting
confidence: 91%
“… 11 − 17 Foliar spraying of 3% urea solution produced a higher number of effective tillers hill –1 than 1% urea spraying. 31 Soil (75%) and foliar (10%) application of urea significantly increased the effective tillers of Binahsail and BRRI dhan46 varieties during the T. aman season. 12 Many studies showed that the soil and foliar application of N increased the number of effective tillers hill –1 in many crops.…”
Section: Resultsmentioning
confidence: 88%
“…However, it is essential to consider both, environmental conditions (Thorburn et al 2017; Dias and Sentelhas 2018; Castro et al 2019) and the N requirement of the plant (de Oliveira et al 2013; Leite et al 2016; Mariano et al 2016) to promote great NUE and NRP, minimizing nitrogen losses, and supporting sustainable agricultural practices (Zhang et al 2015; Bowles et al 2018). Adjusting the timing of N‐fertilizer application (Lofton and Tubaña 2015; de Castro et al 2022) and employing appropriate application methods (Borges et al 2019) have been found to reduce greenhouse gas (GHG) emissions and improve NUE in sugarcane. However, these actions alone are insufficient as a significant proportion of nitrogen becomes immobilized in the soil (Otto et al 2016; Quassi de Castro et al 2021; Sanches and Otto 2022).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of ammonium and urea, which are components of N-urea fertilizers, have been shown to be toxic to plants in prior studies (Krogmeier et al 1989;Tan et al 1999 in 15 NL of all sugarcane varieties studied (Figure 6). This might leads to a probable increase in the ammonium content, which is the primary product of urea hydrolysis (Witte 2011;Castro et al 2022). The assimilation of ammonium into glutamine and glutamate contributes to the accumulation of protons, leading to abiotic stress in plants (Britto and Kronzucker 2005;Masclaux-Daubresse et al 2010;Hachiya et al 2021).…”
Section: Fnf Toxicity Tolerance Differs Between Sugarcane Varietiesmentioning
confidence: 99%
See 1 more Smart Citation